Comparative Anatomy of Axial Skeleton of Red-eared Turtle (Trachemys scripta elegans, Wied 1838) and Softshell Turtle (Amyda cartilaginea, Boddaert 1770) - Mustafa, Hanif; Luthfi, Muhammad Ja’far; Ilmi, Fadhilatul; Khoirunnisa, Ida; Takrima, Takrima (Proceeding International Conference on Science and Engineering, 2019)
Red-eared turtle and softshell turtles belong Cryptodira Suborder which has a different characteristic in neck length and head movement. The aim of this study was to determine of the axial skeleton anatomical structure including vertebrae, carapace and plastron of the red-eared turtle (Trachemys scripta elegans Wied, 1838) and softshell turtles (Amyda cartilaginea Boddaert, 1770) females. This research was carried out for five months starting from September 2013 to January 2014. The methods used in this study were th e X-Ray method, boiled bone and Alizarin Red S-Alcian blue staining. The result of research was analyzed descriptively comparatively by direct observation using a digital camera. Based on the results of the study the Red-eared turtle tortoise has a number of 7 cervical vertebrae, 9th vertebrae, sacral vertebrae 1 segment and vertebrae caudalis 27 segments. The anterior and posterior zygapophysis of the cervix elongate thus affecting the limited lateral movement. The thoracic center of the vertebrae adjusts the shape of the carapace. The sacralis vertebrae have 1 centrum segment extending on the lateral side attached to the carapace called the lateral pars, the caudal centrum is short and there is a shortened anterior zygapophysis structure. Whereas softshell turtles have slender and long centrums. The anterior and posterior zygapophysis are smaller and allow the softshell turtles to perform more lateral movements. Centrum vertebrae of the thorachalis have a flat shape adjusting the shape of the carapace. Sacralis vertebrae have 2 centrum and 2 lateral pars extending and meeting each other to form a hole sacralia pelvina, centrum vertebrae caudalis extends and there is a neural spinal structure. Carapace of the red-eared turtle consists of fused pieces. Whereas the carapace in the softshell turtles consists of pieces covered by cartilage. The constituent component of carapace and plastron of the red-eared turtle consists of true bones completely, while the constituent components of the carapace and plastron of softshell turtles consist of true bones and cartilage on the sides and connective between the carapace and plastron.